Influence of Free Shipping, Discounts, and Online Customer Reviews on Purchasing Decisions at The Twin Date Event: Study on Shopee Online Shopping Community in Bandar Lampung - Ramdani, Rahmat; Rifa'i, Ahmad; Saptiani, Fenny (Journal of Business Management and Economic Development, 2025)
The advancement of digital technology has greatly influenced the commercial sector by enabling seamless online transactions through e-commerce platforms. Shopee emerges as one such platform that offers features like free shipping, attractive discounts, and online customer reviews, all of which have the potential to affect consumer purchasing decisions. The target is to test the impact of free shipping, discounts and online customer reviews on purchasing decisions on twin dating events on the Shopee platform. Employing a quantitative approach with an explanatory research design, the study targets consumers who have made purchases on Shopee and are part of the online shopping community in Bandar Lampung. This study employs a purposive sampling, which falls under the category of non-probability sampling, involving 100 respondents. SPSS 26 was used to analyze data collection through online questionnaires. This research shows the results that purchasing decisions at twin date events on the Shopee platform are each positively and partially influenced by the variables free shipping, discounts and online customer reviews. During a promotional event, purchasing decisions are positively influenced by these three variables when analyzed simultaneously.